2016
DOI: 10.1177/1077546315585424
|View full text |Cite
|
Sign up to set email alerts
|

A novel high-frequency interpretation of a general purpose Op-Amp-based negative resistance for chaotic vibrations in a simple a priori nonchaotic circuit

Abstract: A novel model of general purpose operational amplifiers is made to approximate, at best, the equivalent circuit for real model at high-frequency. With this new model, it appears that certain oscillators, usually studied under ideal considerations or using many existing real models of operational amplifiers, have hidden subtle and attractive chaotic dynamics that have previously been unknown. These can now be revealed. With the new considerations, a ''two-component'' circuit, consisting simply of a capacitor in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 18 publications
1
13
0
Order By: Relevance
“…Recent examples of two-component electronic circuits [41] operating at high frequency [42,43] have been reported. In spite of the simplicity of [43] made solely of a transistor and a tapped coil, Joana et al [44] have revealed the presence of infinite families of spiral phases of stability in its phase diagrams.…”
Section: Introductionmentioning
confidence: 99%
“…Recent examples of two-component electronic circuits [41] operating at high frequency [42,43] have been reported. In spite of the simplicity of [43] made solely of a transistor and a tapped coil, Joana et al [44] have revealed the presence of infinite families of spiral phases of stability in its phase diagrams.…”
Section: Introductionmentioning
confidence: 99%
“…are the corresponding finite times of the usual Lyapunov function derivative. The inequality in equation (27) is derived by integrating the relations in equations (21) and (22).…”
Section: Ftsm Synchronization Of Two Circuits Encoded By An Implicit mentioning
confidence: 99%
“…26 The aim of this section is to achieve the fast finite-time synchronization of two similar systems described by equation ( 1) using a nonlinear sliding surface of the implicit variable g. The nonlinearity of the controller is based on sigmoid function. 27 Generally, the sigmoid function is used in the SMC method to achieve asymptotical convergence of the controlled systems. 2,3,10,11,13,[18][19][20][21][22][23][24][25][26][27][28][29] However, with the advantages offered by jerk equations, the FTSM convergence can be obtained if the sigmoid function is a hyperbolic tangent function.…”
Section: Ftsm Synchronization Of Two Circuits Encoded By An Implicit Equationmentioning
confidence: 99%
“…One of the most active fields for chaos and applications remains that of electronic circuits. Apart from the groundbreaking Chua's circuit [3], many other chaotic circuits have been found, or existing oscillators used to introduce sinusoidal oscillations in curricula have been modified for chaos [16, 17, 18, 19, 20, 21], so that proposing new circuits can now make sense according to Sprott [22], only if they fulfill at least one of the following requirements:Credibly modeling some important unsolved problem in nature and shed insight on that problem;Exhibiting some behavior previously unobserved orBeing simpler than all other known examples exhibiting the observed behavior.…”
Section: Introductionmentioning
confidence: 99%